2020
DOI: 10.1371/journal.pone.0237546
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of the endangered orchid Pelatantheria scolopendrifolia (Orchidaceae) in Korea

Abstract: Due to substantial population decline, the Korean orchid P . scolopendrifolia is considered endangered and highly threatened. Like many endangered species, it is vulnerable to biological and anthropogenic threats that can lead to the loss of genetic diversity and, ultimately, extinction. Therefore, the assessment of genetic diversity and population genetic structure is imperative for conservation. In this study, we newly developed 15 polymorphic microsatellite mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 83 publications
(120 reference statements)
3
9
0
Order By: Relevance
“…A high degree of genetic differentiation among populations accounted for approximately 54% of the total genetic diversity (G ST = 0.544, AMOVA, P=45%), so both withinpopulation diversity and diversity among populations contributed significantly to the total diversity of the species. Other species also showed high diversity among populations, such as Argania spinosa L. Skeels (Mouhaddab et al, 2017), Brasenia schreberi (Li et al, 2018), and Pelatantheria scolopendrifolia (Yun et al, 2020). Yun et al (2020) showed that geographic isolation, low gene flow and asexual reproduction were related to the high divergence among Pelatantheria scolopendrifolia populations.…”
Section: Discussionmentioning
confidence: 96%
“…A high degree of genetic differentiation among populations accounted for approximately 54% of the total genetic diversity (G ST = 0.544, AMOVA, P=45%), so both withinpopulation diversity and diversity among populations contributed significantly to the total diversity of the species. Other species also showed high diversity among populations, such as Argania spinosa L. Skeels (Mouhaddab et al, 2017), Brasenia schreberi (Li et al, 2018), and Pelatantheria scolopendrifolia (Yun et al, 2020). Yun et al (2020) showed that geographic isolation, low gene flow and asexual reproduction were related to the high divergence among Pelatantheria scolopendrifolia populations.…”
Section: Discussionmentioning
confidence: 96%
“…The relationship between Taro and Bali cattle showed that inbreeding had been in existence in the village forest decades ago. Therefore, the greater the variety of haplotype composition in one population, the greater the genetic diversity (Thomas et al 2012;Akbar et al 2014;Yang et al 2019;Yun et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the genetic diversity of bak-kala is relatively low. Genetic diversity is declared high if it has a Shannon index value and diversity close to 1 (Morris et al, 2014;Silva et al, 2015;Yun et al, 2020). The percentage of polymorphic loci (% P) varied between 16.68%-49.35%, with a mean of 27.92%.…”
Section: Issr Polymorphismmentioning
confidence: 99%
“…The recent results indicated that ISSR markers can be used and helpful in recognizing the genetic diversity in bak-kala (E. elatior), and the study also recorded the highest genetic diversity and polymorphisms in bak-kala populations. Information on genetic diversity patterns is essential for designing conservation, management, and sustainable use strategies for plant species (Chung et al, 2013;Liu et al, 2019;Yun et al, 2020). Efforts that need to be made, so that the genetic resources of the future generations continue to grow, are by using an ex-situ conservation approach.…”
Section: Issr Polymorphismmentioning
confidence: 99%